Formulation and Evaluation of Naproxen Sodium Loaded Invasomes for Topical Delivery - Shailaja, Abbaraju K.; Afreen, Uzma (Current Nanomedicine, 2022)
Introduction: Naproxen sodium is a non-steroidal anti-inflammatory agent used in the treatment of rheumatoid arthritis and ankylosing spondylitis to relieve pain and inflammation. It mainly acts by inhibiting COX1 and COX2 receptors. By inhibiting the COX1 receptor, it causes severe gastric bleeding and peptic ulcer, and by inhibiting the COX2 receptor, it causes cardiovascular side effects. In order to avoid the adverse effects of naproxen, there is a need to develop a novel drug delivery system. So that invasomes, because of their vesicular structure, are capable of penetrating more into the systemic circulation and will be acting locally and systemically. Methods: In this study, attempts have been made to prepare and characterize naproxen sodium loaded invasomes. Naproxen sodium loaded invasomes were prepared by thin film hydration technique using soya lecithin as lipid, span60 as surfactant, limonene as terpene and methanol, ethanol and chloroform as organic solvents. A total of twelve formulations (INV1-INV12) of invasomes were prepared, in which four formulations were prepared by varying drug to surfactant ratio and eight formulations were prepared by varying drug to lipid ratio. Results and Discussions: All the formulations were evaluated for drug content, entrapment efficiency, particle size, zeta potential, and invitro drug release. Among the twelve formulations of invasomes, the INV2 formulation (1:1) ratio containing 40mg drug and 40mg surfactant (span60) was found to be the best formulation with a drug content of 96.62%, entrapment efficiency of 90.9%, zeta potential of -68.5mV, mean particle diameter of 572.4 nm, and invitro drug release of 91.6% in a time period of 12 hrs and followed the zero order kinetics with non fickian diffusion mechanism. Conclusion: In this present study, naproxen sodium loaded invasomes were successfully prepared and evaluated.
Keywords: limonene